Enhancing Indonesian Language Skills through Exploratory Learning: A Study at MIN 2 Lembata - Siti Salehah; Susanti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to explore the effectiveness of exploratory learning in enhancing Indonesian language skills at MIN 2 Lembata. As language development is crucial in early education, it is important to implement methods that engage students actively and promote critical thinking. Exploratory learning, which encourages students to investigate, inquire, and actively participate in discovering new knowledge, is believed to foster a deeper understanding and more meaningful learning experience. This research focuses on the application of exploratory learning strategies to improve students’ reading, writing, speaking, and listening skills in the Indonesian language. The study was conducted with 4th-grade students at MIN 2 Lembata, with data collected through a combination of pre- and post-assessments, classroom observations, and interviews with both teachers and students. The pre-assessment aimed to evaluate students’ initial proficiency in the Indonesian language, while the post-assessment measured their progress after the implementation of exploratory learning. Classroom observations provided insights into student engagement and participation, while interviews helped to gather feedback on their learning experiences. The findings indicate that exploratory learning significantly improved students’ Indonesian language skills. Students showed greater involvement in discussions, developed better communication skills, and demonstrated improved ability to analyze and express ideas. Teachers also reported an increase in student motivation and enthusiasm for learning. This research suggests that exploratory learning is an effective approach to enhance Indonesian language skills, creating a more engaging and interactive classroom environment for students at MIN 2 Lembata.